The computer-aided design of windows as passive solar collectors - 227582 Milne, Murray; University of California, Los Angeles. School of Architecture and Urban Planning; International Solar Energy Society Conference (1977 : Orlando) (Los Angeles : School of Architecture and Urban Planning, University of California, 1977)
03